Peranan Etika Bisnis dalam Perusahaan Maspion - Adelia Pratiwi, Anggun; Kurniawan, Taufik (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Applied ethics includes a branch called "business ethics" that aims to keep tabs on a company's morals and ethics under tight scrutiny. Business ethics and effective management are crucial, but they are not the main determinants of a company's success. The business sector is very competitive, and ethics in the workplace are taken for granted. Regardless of whether the information is good or bad, it can spread swiftly. Businesses can only exist if they treat their customers and suppliers with respect, as well as their investors and the general public. The fierce competition in business leads to a lack of attention to corporate ethics on the part of executives.